Engineered bamboo bridge structure - Report on 3rd International Collaboration on Bamboo Construction - Haitao Li; Zixian Feng; Xinqi Shen; Yifan Wang; Xin Xue; Rodolfo Lorenzo; Mahmud Ashraf; Zhenhua Xiong; Chungui Zhou; Ningjun Chen; Jian Zhang; Kewei Liu; et al. (Sustainable Structures)
Engineered bamboo has attracted more and more scientists’ and engineers’ attention in construction field. In order to show the application in bridge structures, the 3rd International Collaboration on Bamboo Construction, jointly organized by Nanjing Forestry University, University College London and International Bamboo and Rattan Organization (INBAR), was held on the campus of Nanjing Forestry University. During the event, Chinese teachers and students as well as some experts from industry, together with international teachers and students, successfully constructed a 12-meter-long reciprocal bridge made of engineered bamboo without using any large mechanical equipment. The main structure of the bamboo bridge was made of laminated bamboo lumber (LBL), and then bamboo scrimber (BS) panels were laid to form the bridge deck. Traditional Chinese mortise and tenon connection was adopted to connect the components of the main structure instead of metal connections. The purpose of this construction event was to demonstrate the feasibility and stability of a large-span engineered bamboo structure as a practical engineering reference for the development of engineered bamboo in the field of construction engineering.